Bindle punk Jefe : a novel - Mesa, Desideria (Harper Voyager, 2024)
Prohibition is in full swing, and the glamorous life of upper-class Kansas City is everything Rose (Luna) Lane ever hoped it would be. Being married to her best friend isn't so bad either, considering their agreement to keep their real love lives out of the public eye. However, try as she might to continue her life of anonymity, her popularity as a land developer's wife--and as a successful club owner--draws even more attention to her personal endeavors. Soon, the balancing act between the life of Luna and Rose becomes a full-time job itself, making visiting home harder than ever before. However, her haven, which once offered a place of acceptance, is growing more hostile. Her community of brujas criticizes her methods of using magic for economic and social gain while consorting with nefarious witches of the North. Meanwhile, the Pendergast Machine is running at full force, pushing his will and money all over the city. Keeping her true identity and powers a secret while posing for the society papers gets all the more dangerous as new enemies start to question her origins...and old ones creep up from dark realms. The pressure could force Rose to do questionable things for the greater good, distancing herself from her loved ones and who she wants to be. She may have mastered her earth magic, but she still has a lot to learn about the heart...